Introduction to Distributed Computer Systems Principles and Features - Czaja, Ludwik (Lecture Notes in Networks and Systems,, 2018)
This book introduces readers to selected issues in distributed systems, and primarily focuses on principles, not on technical details. Though the systems discussed are based on existing (von Neumann) computer architectures, the book also touches on emerging processing paradigms. Uniquely, it approaches system components not only as static constructs, but also "in action," exploring the different states they pass through. The author's teaching experience shows that newcomers to the field, students and even IT professionals can far more readily grasp the essence of distributed algorithmic structures in action, than on the basis of static descriptions.